Carbon monoxide and water vapor in the atmosphere of the non-transiting exoplanet HD 179949 b - Brogi, M.; de Kok, R. J.; Birkby, J. L.; Schwarz, H.; Snellen, I. A. G. (Astronomy and astrophysics (Berlin), 2014)
Context. In recent years, ground-based high-resolution spectroscopy has become a powerful tool for investigating exoplanet atmospheres. It allows the robust identification of molecular species, and it can be applied to both transiting and non-transiting planets. Radial-velocity measurements of the star HD 179949 indicate the presence of a giant planet companion in a close-in orbit. The system is bright enough to be an ideal target for near-infrared, high-resolution spectroscopy. Aims. Here we present the analysis of spectra of the system at 2.3 μm, obtained at a resolution of R ~ 100 000, during three nights of observations with CRIRES at the VLT. We targeted the system while the exoplanet was near superior conjunction, aiming to detect the planet’s thermal spectrum and the radial component of its orbital velocity. Methods. Unlike the telluric signal, the planet signal is subject to a changing Doppler shift during the observations. This is due to the changing radial component of the planet orbital velocity, which is on the order of 100–150 km s-1 for these hot Jupiters. We can therefore effectively remove the telluric absorption while preserving the planet signal, which is then extracted from the data by cross correlation with a range of model spectra for the planet atmosphere. Results. We detect molecular absorption from carbon monoxide and water vapor with a combined signal-to-noise ratio (S/N) of 6.3, at a projected planet orbital velocity of KP = (142.8 ± 3.4) km s-1, which translates into a planet mass of MP = (0.98 ± 0.04) Jupiter masses, and an orbital inclination of i = (67.7 ± 4.3) degrees, using the known stellar radial velocity and stellar mass. The detection of absorption features rather than emission means that, despite being highly irradiated, HD 179949 b does not have an atmospheric temperature inversion in the probed range of pressures and temperatures. Since the host star is active (R'HK > -4.9), this is in line with the hypothesis that stellar activity damps the onset of thermal inversion layers owing to UV flux photo-dissociating high-altitude, optical absorbers. Finally, our analysis favors an oxygen-rich atmosphere for HD 179949 b, although a carbon-rich planet cannot be statistically ruled out based on these data alone.